Development of method of express internal combustion engine diagnosis based on wavelet analysis - Тыманюк, Константин Сергеевич; Костенко, Виталий Леонидович; Николенко, Анатолий Александрович; Теплечук, Анатолий Михайлович; Адаменко, Денис Олегович (Technology audit and production reserves, 2016)
The method of rapid internal combustion engine diagnosis based on wavelet analysis of vibration signals during maintenance using automated parallel data collection systems is proposed. Software for processing and analyzing the diagnostic data is developed In the MATLAB environment. The experimental validation of the developed method is conducted. Analysis of experimental data allowed determining the defective engines using the vibration signal. Diagnostic signals containing a frequency map of nondefective internal combustion engine VAZ are obtained during experiment, which allowed determining the deviation from the norm in diagnosed engines. Disadvantages at this stage of the research include the need for storage of diagnostic information for each type of fault. Such information later will reduce the time of rapid diagnostic procedures and extend its capabilities. There is also a disadvantage is the need to expand the range of diagnosed internal combustion engine types. Comparative analysis of the examples of initial diagnostic signals and their wavelet decompositions showed the possibility of further use of the data for rapid internal combustion engine diagnosis. The possibility of method will be substantially expanded with the accumulation of diagnostic features and improving the software, because the processes in internal combustion engines generate the necessary information about its technical condition as vibratory activity. The research results can be useful for assessing the technical condition of the engines.